Plasmacytoid Dendritic Cells Respond Directly to Apoptotic Cells by Secreting Immune Regulatory IL-10 or IFN-α - Simpson, Joanne (Front Immunol, 2016)
Plasmacytoid dendritic cells (pDCs) play a pivotal role in driving the autoimmune disease systemic lupus erythematosus, via the secretion of IFN-α in response to nuclear self-antigens complexed with autoantibodies. Apoptotic cells, generated at sites of inflammation or secondary lymphoid organs, are exposed to activated pDCs and also express the same nuclear antigens on their cell surface. Here, we show that in the absence of autoantibodies, activated pDCs directly respond to apoptotic cell-expressed chromatin complexes by secreting IL-10 and IL-6, which also induces T cells to secrete IL-10. Conversely, when activated by the viral mimetic CpG-A, apoptotic cells enhance their secretion of IFN-α. This study demonstrates that activated pDCs respond directly to apoptotic cells and may maintain tolerance via IL-10, or promote inflammation through secretion of IFN-α, depending on the inflammatory context.